1996
DOI: 10.3109/09273949609079647
|View full text |Cite
|
Sign up to set email alerts
|

Nicardipine Inhibits Acute Rise of Aqueous Flare and Intraocular Pressure Induced by Argon Laser Photocoagulation

Abstract: The purpose of this study was to examine the anti-inflammatory effect of the calcium channel blocker nicardipine. Intraocular inflammation was induced by argon laser photocoagulation of the iris of pigmented rabbits and was assessed by measuring aqueous flare and intraocular pressure. This resulted in a marked increase in the aqueous flare that peaked at approximately one hour following coagulation and returning to the original values after six hours. Intraocular pressure increased within 15 minutes following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…We also reported that intravenous nicardipine, 2 mg/kg body weight, inhibited the acute rise of aqueous flare and intraocular pressure induced by argon laser photocoagulation in pigmented rabbits [3]. We further showed that when 50 Ìg/ml of PGE 2 was applied every day for 6 days, the flare intensity decreased significantly day by day [4].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…We also reported that intravenous nicardipine, 2 mg/kg body weight, inhibited the acute rise of aqueous flare and intraocular pressure induced by argon laser photocoagulation in pigmented rabbits [3]. We further showed that when 50 Ìg/ml of PGE 2 was applied every day for 6 days, the flare intensity decreased significantly day by day [4].…”
Section: Introductionmentioning
confidence: 66%
“…The measurement was taken in the midportion of the anterior chamber. The sampling area was 0.075 mm 3 . Aqueous flare elevation is expressed as the area under the curve (AUC) and inhibition is estimated by the following equation: Those who carried out the measurements were not informed about the treatment.…”
Section: Aqueous Flare Measurementmentioning
confidence: 99%
“…Not all calcium channel blockers inhibit the acute rise of aqueous flare induced by PGE 2 in rabbits [3][4][5]. Chang et al [8] reported that nifedipine and nisoldipine (calcium channel blockers) inhibited the activity of phospholipase A 2 in a cell-free preparation of human platelets that acts on the release of arachidonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators demonstrated that some kinds of calcium channel blockers inhibit the experimental inflammation: Kaji et al [3,4] showed that intravenously administered nicardipine (a calcium channel blocker), 2 mg/kg body weight, inhibited the acute rise of aqueous flare induced by PGE 2 and laser irradiation to the iris. Nilvadipine, 5-isopropyl-3-methyl-2-cyano-1,4-dihydro-6-methyl-4-(m-nitrophenyl)-3,5-pyridinedicarboxylate, is another calcium channel blocker and is clinically used for the treatment of systemic hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In 1994, Kaji et al [1] showed that nicardipine, 1,000 Ìg/kg, suppressed the prostaglandin-E 2 -induced flare elevation. In 1996, Kaji et al [2] demonstrated that nicardipine, 2,000 Ìg/kg, inhibited the photocoagulation-induced flare rise. In 1998, Zhang et al [3] reported that nilvadipine, 5-500 Ìg/kg, inhibited the PGE 2 -induced flare elevation.…”
Section: Introductionmentioning
confidence: 99%